Endovascular repair of blunt thoracic aortic injury - Gustavo Stringel; Min Li Xu; Markus Erb (Elsevier, 2018)
Traumatic thoracic aortic injuries are rare in the pediatric population. Most patients sustaining this injury do not survive and succumb at the scene. Associated injuries can complicate the management of the aortic injury. Aortic injuries have traditionally been treated by open repair. In the adult population, endovascular stenting has become the management of choice. The pediatric literature has isolated reports of the use of endovascular stenting in the repair of aortic injuries. We report an 11 year old female with multiple injuries and a grade III thoracic rupture with a pseudoaneurysm successfully managed with endovascular stenting.